Affixing the theory of normative conduct (to your mailbox): Injunctive and descriptive norms as predictors of anti-ads sticker use. (December 2015) - Hamann, Karen R.S.; Reese, Gerhard; Seewald, Daniel; Loeschinger, Daniel C.
Abstract: Pro-environmental behavior is strongly influenced by social norms. In this field experiment, we tested both injunctive and descriptive norms' influence on the decision to attach an anti-ads sticker to one's mailbox. In a natural setting with N  = 383 households, we manipulated the salience of a descriptive norm and the salience of several injunctive norms, the latter with both a general and a local reference frame, and collected data about the descriptive norm strength. In line with our expectations, the combination of salient pro-environmental descriptive and injunctive norms caused the highest sticker attachment rates. An injunctive norm with a general reference frame turned out to be most effective. Moreover, our findings suggest that norm conflict produces similar results as low norm salience. We discuss theoretical developments, the role of reference frames as a function of neighborhood, and give advice to practitioners. Highlights: The contribution of social norms on pro-environmental behavior (PEB) were tested in a field experiment. Combining pro-environmental descriptive and salient pro-environmental injunctive norms resulted in strongest PEB rates. An injunctive norm with a general, rather than local, reference frame turned out to be the most effective. Norm conflict between descriptive and injunctive norms show similar results as low norm salience. Long-term consequences of norms could be identified.